Study on the alkaloids of Anona squamosa Linne (Family Anonaceae) - Talain, Estrella C.
The alkaloids of Anona squamosa Linne (Family Anonaceae) was studied using different methods which were learned in our previous pharmacy and chemistry courses. Among the techniques employed were melting point determination, thin-layer chromatography and spectrophotometric techniques of analysis.